FAKTOR-FAKTOR FEDERASI RUSIA TIDAK MENGIMPLEMENTASIKAN CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN(CEDAW) DALAM MENGATASI KEKERASAN RUMAH TANGGA2010-2016 - Elsa Riana; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Violence against women has now become a serious threat and is part of human rights violations. The Convention on the elimination of all forms of discrimination against Women (CEDAW) is one of the international conventions under the United Nations concerning the elimination of all forms of discrimination against women both in the social, political, economic and cultural fields. Russia is one of the parties to the CEDAW convention, which prohibits violence against women both in the public and private spheres and establishes such violence as a form of discrimination. But based on the fact that domestic violence is one of the most frequent discrimination against women in the Russian Federation, it causes Russian women to die and experience severe trauma. In this study the author uses the theory of Radical Feminism. according to kate millet through his theory, "sexual politics" (sexual politics) shows how the position of men is more dominant than women in patriarchal society. Sexual politics is defined as the politicization of power based on gender or gender. The hegemony of masculinity and the subordination of femininity are illustrated through inequality in the distribution of character, role, and status between feminine and masculine. The Government of the Russian Federation is less responsive in dealing with violence or discrimination faced by women in the household. This is influenced by patriarchal cultural factors that are still deeply rooted since the Empire until the current federation. In the legal regulations the Russian government itself does not bind strong rules against perpetrators of domestic discrimination, the Government's legal rules do not work in accordance with the CEDAW convention and the government does not maintain data on cases of female violence that occur in Russia.  Keywords: Domestic Violence, Women, Russian Federation, CEDAW, Human Rights.